2009
DOI: 10.1177/0218492309103302
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Aortoplasty for Ascending Aortic Aneurysm: A 14-Year Experience

Abstract: We present early results and long-term follow-up after reduction aortoplasty with external wrapping of the ascending aorta. From December 1993 to February 2008, 32 consecutive patients who had reduction aortoplasty were compared with 47 consecutive patients who underwent prosthetic graft replacement of the ascending aorta. The groups were similar in baseline characteristics. Patients in the reduction aortoplasty group had significantly shorter aortic crossclamp times (18.78 +/- 1.91 vs. 34.04 +/- 3.25 min) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 11 publications
(16 reference statements)
2
30
0
Order By: Relevance
“…The causes are not known, but in view of concomitant combined cardiac procedures, connections to the underlying cardiac disease can be derived. The results are comparable with those of other studies [2,8,9]. Bauer et al [13] reports a survival rate of 94% after 5 years and regards the aortoplasty-related mortality as very low.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The causes are not known, but in view of concomitant combined cardiac procedures, connections to the underlying cardiac disease can be derived. The results are comparable with those of other studies [2,8,9]. Bauer et al [13] reports a survival rate of 94% after 5 years and regards the aortoplasty-related mortality as very low.…”
Section: Discussionsupporting
confidence: 87%
“…This is a viable procedure which has demonstrated a number of advantages (less invasive as compared to replacement with a Dacron graft, shorter aortic clamping time, lower risk of bleeding) [6][7][8]. In addition, lower mortalities and morbidities were reported in patients with RAA [9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that ascending aorta aortoplasty with external reinforcement is a safe procedure with excellent long-term results and that it is a therapeutic option in patients with poststenotic dilatation of the aorta, without dilatation of the sinotubular junction. Belov (Belov et al, 2009), in 2009, compared the early results and late outcome in two groups of patients. Group 1 had prosthetic ascending aorta replacement, while group 2 had reduction aortoplasty and external wrapping.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…This is a viable procedure which has demonstrated a number of advantages (less invasive as compared to replacement with a Dacron graft, shorter aortic clamping time, lower risk of bleeding) [6-8]. In addition, lower mortalities and morbidities were reported in patients with RAA [9].…”
Section: Introductionmentioning
confidence: 99%
“…[2]. Reduction ascending aortoplasty is often used in older patients with non-dissecting aortic aneurysm, in particular as an added procedure with concomitant cardiosurgical intervention [8,9]. …”
Section: Introductionmentioning
confidence: 99%